Answer:
a
Step-by-step explanation:
Answer:
-9
Step-by-step explanation:
Distance formula : d = sqrt (x2 - x1)^2 + (y2 - y1)^2
(-5,8)(10,-7)
d = sqrt (10 - (-5)^2 + (-7 - 8)^2
d = sqrt (10 + 5)^2 + (- 15^2)
d = sqrt (15^2) + (-15^2)
d = sqrt 225 + 225
d = sqrt 450
d = 21.21
Answer:
and
Step-by-step explanation:
A simple way to solve this problem is to plug the corresponding x and y into the function. We need only one pair since all the functions are quasi-linear (y=kx) and the increase is proportional.
In when x=3, y=15/4≈2.14
In when x=3, y=1.8
In when x=3, y≈2.33
In when x=3, y≈1.90
We can observe that in two cases, and , y is greater than 2.
Answer:
dang thats tough
Step-by-step explanation: